An explorative study on meaningful brand strategies to curb food waste – a Food Lover’s Market case study - Lekalakala, Boitumelo (The IIE, 2022)
Consumers waste a lot of food bought on special and are used to high quality standards on products that retail stores uphold. This study explores more meaningful brand practices that Food Lover’s Market can utilise in order to reduce food waste in store and this resulting in consumers reducing food waste at home too. This exploration was done through a mixed method study using content analysis of discussions on Facebook and Twitter posts, and a survey. The main aim of the research was to evaluate people’s thoughts about the brand, people’s thoughts about fresh produce, to investigate the quality standards that retail stores uphold and understand how effecting certain changes could possibly make crooked shaped produce “cool” to reduce food waste and look at other strategies Food Lover’s Market can adapt to be more meaningful as promotions such as buy one get one free have been shunned upon as contributors to food waste. The study made reference to secondary sources to support the phenomenon that there are other meaningful practices that other brands are doing globally to reduce food waste. Furthermore, that consumers waste a lot of food because they bought it on special and that retail stores have high quality standards allowing them to throw away fresh food because of shape. This study took a coding analysis approach for the content analysis from Twitter and Facebook and took the Miles and Huberman approach to analyse the content from the survey. All the data collected was then coded into themes addressing the research objectives. The first data set was collected through a survey completed by a total of fifty-two participants over five days. The second data set was collected through online searching of discussions on social media about Food Waste and Food Lover’s Market. This information was interpreted qualitatively and quantitively to achieve triangulation and validity. This study formulated recommendations for Food Lover’s Market and other retail brands to utilise in order to reduce food waste by not letting fresh food go to waste simply because of shape. Furthermore, it recommended the need to ease consumers into the idea of community sharing as consumers waste a lot of food as a result of not having anyone to share the food with. Lastly, it formulated recommendations about brand communication to consumers regarding the life span of products as a more meaningful brand practice.
Keywords: Technology; Consumer behaviour; Social media; Meaningful brands; Hunger